2013
DOI: 10.1007/s10886-013-0244-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Soil Feedbacks and Soil Sickness: From Mechanisms to Application in Agriculture

Abstract: Negative plant-soil feedbacks play an important role in soil sickness, which is one of the factors limiting the sustainable development of intensive agriculture. Various factors, such as the buildup of pests in the soil, disorder in physico-chemical soil properties, autotoxicity, and other unknown factors may contribute to soil sickness. A range of autotoxins have been identified, and these exhibit their allelopathic potential by influencing cell division, water and ion uptake, dark respiration, ATP synthesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
206
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(209 citation statements)
references
References 103 publications
1
206
0
2
Order By: Relevance
“…Plants can influence soil properties and soil organisms via releasing low-molecular mass compounds(sugars, amino acids and organic acids) and dead roots, in turn modifying plant performance through mutualistic interactions, nutrition availability, or pathogenic activity, etc. (Berg and Smalla, 2009;Jones et al, 2009;Huang et al, 2013). Although the reasons for poor growth and reduced yields caused by Table 2; ‡Reference soil collected from a neighboring field with the same soil type but without growing Chuju Table 2 continuous monocropping are complicated and have not been clearly defined, they may be summarized as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Plants can influence soil properties and soil organisms via releasing low-molecular mass compounds(sugars, amino acids and organic acids) and dead roots, in turn modifying plant performance through mutualistic interactions, nutrition availability, or pathogenic activity, etc. (Berg and Smalla, 2009;Jones et al, 2009;Huang et al, 2013). Although the reasons for poor growth and reduced yields caused by Table 2; ‡Reference soil collected from a neighboring field with the same soil type but without growing Chuju Table 2 continuous monocropping are complicated and have not been clearly defined, they may be summarized as follows:…”
Section: Discussionmentioning
confidence: 99%
“…The exact causes of soil sickness represent a continued focus of research activity (Mazzola and Manici 2012;Huang et al 2013). Various factors, such as the accumulation of phytotoxins, ion imbalances in the soil, or pathogen abundance, have been suggested as possible causes of this problem, yet differences exist relative to the functional diseasecausing agents (Rumberger et al 2007; Mazzola and Manici Electronic supplementary material The online version of this article (doi:10.1007/s00374-015-1038-8) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on the shift in the microbial community in rhizosphere soil with the replant problem. [1,9À11] Huang et al [12] found that autotoxins influence soil microbes, leading to an increased or decreased degree of soil sickness.…”
Section: Introductionmentioning
confidence: 99%